1) Solution is (x, y) = (7, 11)
2) Solution is (x, y) = (4, 1)
3) Solution is (x, y) = (0.5, 12.5)
4) Solution is (0.25, 5.5)
Solution:
1)
y = 2x - 3 ------- eqn 1
x + y = 18 -------- eqn 2
Rearrange eqn 1
2x - y = 3 ------- eqn 3
Add eqn 2 and eqn 3
x + y = 18
2x - y = 3
( + ) ------------
3x = 21
x = 7
Substitute x = 7 in eqn 1
y = 2(7) - 3
y = 14 - 3
y = 11
Thus solution is (x, y) = (7, 11)
2)
y = 0.25x ------ eqn 1
x + 4y = 8 ---------- eqn 2
Rearrange eqn 1,
0.25x - y = 0 ------- eqn 3
Multiply eqn 3 by 4
x - 4y = 0 ---- eqn 4
Add eqn 2 and eqn 4
x + 4y = 8
x - 4y = 0
( + ) -------------
2x = 8
x = 4
Substitute x = 4 in eqn 1
y = 0.25(4)
y = 1
Thus solution is (x, y) = (4, 1)
3.)
y = x + 12 ------- eqn 1
4x + 2y = 27 --------- eqn 2
Rearrange eqn 1,
x - y = -12
Multiply above by 2
2x - 2y = -24 ------- eqn 3
Add eqn 2 and eqn 3
4x + 2y = 27
2x - 2y = -24
( + ) ---------------
6x = 3
x = 0.5
Substitute x = 0.5 in eqn 1
y = 0.5 + 12
y = 12.5
Thus solution is (x, y) = (0.5, 12.5)
4.)
10x + 3y = 19 -------- eqn 1
y = 2x + 5 --------- eqn 2
Rearrange eqn 2
2x - y = -5
Multiply above equation by 3
6x - 3y = -15 ------- eqn 3
Add eqn 1 and eqn 3
10x + 3y = 19
6x - 3y = -15
( + ) ----------------
16x = 4
x = 0.25
Substitute x = 0.25 in eqn 2
y = 2(0.25) + 5
y = 5.5
Thus solution is (0.25, 5.5)